Obesity and Premature Loss of Mobility in Two Adolescents with Becker Muscular Dystrophy After HeartMate II Implantation. Issue 1 (January 2016) - Hollander, Seth A.; Rizzuto, Sandra; Hollander, Amanda M.; Lin, Aileen; Liu, Esther; Murray, Jenna M.; Almond, Christopher S.; Rosenthal, David N.
Abstract : Weight gain is common after implantation of continuous-flow ventricular assist devices. Obesity can have a significant negative impact on mobility. For adolescents with Becker muscular dystrophy (BMD), for whom the ability to ambulate often persists into the mid-3rd decade, preservation of functional ability is critical. We report two cases of Thoratec HeartMate II left ventricular assist device (LVAD) implantation in adolescents with BMD for whom postoperative weight gain contributed significantly to an accelerated loss of ambulation and, in one case, driveline fracture in the context of repeated falls. As LVADs become an increasingly common therapy for endstage heart failure in adolescents with BMD, care must be focused not only on maintenance of device functionality, but also on management of aggressive weight, and preservation of ambulation, and skeletal muscle strength.